Compositional, Contextual, and Collective Community Factors in Mental Health and Well-Being in Australian Rural Communities. (April 2017) - Collins, Jessica; Ward, Bernadette M.; Snow, Pamela; Kippen, Sandra; Judd, Fiona
There are disproportionately higher and inconsistently distributed rates of recorded suicides in rural areas. Patterns of rural suicide are well documented, but they remain poorly understood. Geographic variations in physical and mental health can be understood through the combination of compositional, contextual, and collective factors pertaining to particular places. The aim of this study was to explore the role of "place" contributing to suicide rates in rural communities. Seventeen mental health professionals participated in semi-structured in-depth interviews. Principles of grounded theory were used to guide the analysis. Compositional themes were demographics and perceived mental health issues; contextual themes were physical environment, employment, housing, and mental health services; and collective themes were town identity, community values, social cohesion, perceptions of safety, and attitudes to mental illness. It is proposed that connectedness may be the underlying mechanism by which compositional, contextual, and collective factors influence mental health and well-being in rural communities.